Retrospective analytical evaluation of perfomance activities of businessstructures - Alla Moskovchuk; Viktoria Dorosh (Економічний форум)
The article examines indicator systems used to assess the performance of enterprises and methodical approaches to their analysis. The choice of such methods of analytical research, which will give their full assessment and ensure obtaining sufficient information for making management decisions, is justified. It was found that effectiveness is characterized by achievement of the expected state of the entity, management goal, or the degree of approaching it. It isrelated to production, technological and management processes. Internal and external factors influence the effectiveness of the company's activity, their influence is measured by a system of indicators. Currently, a significant number of methods (indicator systems) for measuring the performance of enterprises have been developed by foreign and domestic scientists, which include financial and non-financial indicators. In Ukraine, considerable attention is paid to the analysis of financial performance indicators of business structures. The importance of conducting an analytical study of income, expenses, profit and profitability for domestic producers, the purpose and task of the analytical study is justified. The importance of using factor analysis of performance indicators has been determined. Indicators of income, expenses, profit and profitability are determined on the basis of deterministic factor models. For the purpose of their calculation additive (revenues, expenses, profit) and multiple (profitability) models are built based on the financial statements. In order to determine the impact of factors the methods of integration and proportional division are used. It should be noted that the obtained results of the factor analysis provide sufficient information to the management of the enterprise to manage income, expenses and profit. The results of the study may be useful in the process of developing scientifically based recommendations for the use of analysis tools for making management decisions